Islamic insurance : a review and research agenda - Wang, Tong; Muhammad, Ali; Puah, Chin Hong; Leong, Choi Meng; Xiao, Yuping (Springer Nature, 2024)
This study explores relevant studies on Islamic insurance, including key themes, research areas, and research objectives. This study lays foundation for understanding the current status and trends in Islamic insurance research by systematically collecting, organizing and analyzing relevant literature. This study combines systematic literature review and bibliometric analysis to provide insights into the key research dimensions of Islamic insurance. Using systematic literature review, this study identifes research trends in the topic of Islamic insurance from 2003 to 2023 by systematically analyzing 502 articles in the Scopus database. Using bibliometric analysis, this study reveals the publication trends, infuential articles, and research collaborations in this research area through visual charts and graphs. On this basis, this study analyzes and summarizes four clusters of Islamic insurance research themes focusing on the development and social impact of Islamic insurance in Indonesia; role of Islamic insurance in improving human health security, impact, and diferential study of Islamic insurance on public health education among adult male and female; and religious attitudes and health care access. Emerging themes in the research area were identifed through a thematic analysis of the literature of the last fve years. The study has important implications for practice and policy formulation in the Islamic insurance industry. Through the study of Islamic insurance, it is possible to promote multicultural knowledge exchange and bring a broader perspective to the feld of fnance. Gaps exist in recent literature, comprise the lack of exploration on innovative characteristics in Islamic insurance models from conceptual perspective, impact of Islamic insurance on sustainable development from content perspective and impact of cultural and geographical factors on market development of Islamic insurance from contextual perspective. This study also proposes potential research directions to address these gaps.